In-vitro drug release testing of parenteral formulations via an agarose gel envelope to closer mimic tissue firmness - Kožák, Jan; Rabišková, Miloslava; Lamprecht, Alf (International journal of pharmaceutics, 2021)
Current in vitro drug-release testing of the sustained-release parenterals represents the in vivo situation insufficiently. In this work, a thin agarose hydrogel layer surrounding the tested dosage form was proposed to mimic the tissue. The method was applied on implantable formulations of different geometries (films, microspheres, and cylindrical implants); prepared from various polymers (several Resomer® grades or ethyl cellulose) and loaded with different model drugs: flurbiprofen, lidocaine or risperidone. The hydrogel layer did not possess any retarding effect on the released drug and acted as a physical restriction to swelling and/or plastic deformation of the tested dosage forms. This led to a different surface area available for drug-release compared with testing in release medium alone and correspondingly to significantly different release profiles of the majority of the formulations obtained between the two methods (e.g. t50% = 18 days in pure release medium vs. t50% = 26 days in gel-setup for risperidone loaded Resomer® 503 H films or t50% = 7 days vs. t50% = 19 days for risperidone loaded Resomer® 503 H microspheres). The limited space for swelling and the rigidity of the agarose gel might mimic the tight encapsulation of the dosage form in the tissue better than the conventional liquid medium.
Keywords: velikost částic; In-vitro; kopolymer kyseliny glykolové a mléčné; Particle Size; Lactic Acid; kyselina mléčná; Drug release; Agarose; Hydrogel; Implants; Drug Liberation; Sepharose; sefarosa; Biorelevant; kyselina polyglykolová; Polyglycolic Acid; Polylactic Acid-Polyglycolic Acid Copolymer; PLGA; uvolňování léčiv; Microspheres; mikrosféry